2011
DOI: 10.1007/s00421-011-2208-5
|View full text |Cite
|
Sign up to set email alerts
|

Incline plyometrics-induced improvement of jumping performance

Abstract: The aim of this study was to examine the effects of incline plyometrics training on muscle activation and architecture during vertical jumping and maximum strength. Twenty male participants were divided in two training groups which followed after a 4 week training program. The incline plyometrics group (n = 10) trained by performing consecutive jumps on an inclined surface (15°) while the plane plyometrics (PP) group (n = 10) performed the same jumps on a plane surface. Both groups trained four times per week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…For example, Kyrolainen et al 25) reported that maximal voluntary knee extension torque did not change after a 15-week plyometric training regimen. Additionally, Kannas et al 26) observed no significant increase in maximal voluntary plantar flexion torque.…”
Section: Maximum Strength and Rate Of Force Developmentmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, Kyrolainen et al 25) reported that maximal voluntary knee extension torque did not change after a 15-week plyometric training regimen. Additionally, Kannas et al 26) observed no significant increase in maximal voluntary plantar flexion torque.…”
Section: Maximum Strength and Rate Of Force Developmentmentioning
confidence: 94%
“…Foure et al 34) reported that the fascicle length and pennation angle of the triceps surae muscles did not change after 14 weeks of plyometric training. Kannas et al 26) also reported no significant change in fascicle length or pennation angle of the medial gastrocnemius muscle after 4 weeks of hopping training. In contrast, Blazevich et al 37) reported increased fascicle length and decreased pennation angle of the vastus lateralis muscle after a 5-week plyometric training regimen.…”
Section: Maximum Strength and Rate Of Force Developmentmentioning
confidence: 95%
See 2 more Smart Citations
“…There were other studies that investigated the relationship between muscle stiffness and muscle strength 11) , or investigated changes in ankle angle 10) , and several other studies 12,13) . However, changes in muscle structures such as fascicle length (FL) and pennation angle by PT were not identified 14,15) . In many studies 4,9,10) , that involved exercises consisting of whole-body training such as a counter-movement jump and depth jump, it was guessed which could easily compensate for weak muscles.…”
Section: Introductionmentioning
confidence: 99%